NUMERICAL SIMULATION OF RETROFITTED MASONRY BUILDINGS: RETROFITTING SOLUTIONS FOR UNREINFORCED MASONRY BUILDINGS - Cosme, Samuel Alexandre Corado (2022)
Unreinforced masonry buildings are very common all over Europe, including Portugal and Switzerland. Old and unreinforced masonry buildings are typically constructed with stone masonry and timber floors. The in-plane stiffness and the fixing connections of these floors can have a considerable impact on the global seismic response of the building. As these build- ings are normally considered cultural heritage, their safety and the preservation of their orig- inal characteristics are key elements to consider. The main objective of this thesis is to evaluate and study the behaviour of timber floors, con- sidering possible retrofitting and reinforcement interventions, to enhance the building's re- sistance to seismic events. For this purpose, two numerical models were created, using the software OpenSEES (Open System for Earthquake Engineering Simulation). The first model replicates the original characteristics of unreinforced masonry buildings with stone masonry walls and timber floors. The second model simulates strengthening techniques that are used to enhance the seismic response of the building. The models were developed based on an experimental campaign performed on two half-scale building specimens. Similar to what hap- pens in the development of the numerical models, the first experimental specimen was built based on the typical characteristics of unreinforced masonry buildings. After the first set of experimental tests, this specimen was strengthened. These experimental models were devel- oped and constructed in Athens and were used for a set of shake table tests. The experimental data obtained on these tests is present in the paper Vintzileou and Mouzakis, 2014 [14]. All the data present in this paper was used for the validation of the numerical models. The two numerical models were calibrated and subjected to a set of incremental dynamic analyses that replicate the ground motion used in the experimental shake-table tests. After the analyses, conclusions, and results about the behaviour of the timber floors and the seismic enhancement of the retrofitting interventions are presented.